TEACHERS’ PREPARATION TO THE INFORMATION AND COMMUNICATION TECHNOLOGIES USAGE WITHIN POSTGRADUATE PEDAGOGICAL EDUCATION SYSTEM - Stepan P. Labudko (Information technologies and learning tools, 2011)
Nowadays the question about teachers’ preparation to the information and communication technologies usage during the postgraduate period is actual. Some aspects of academic teachers’ preparation to the information and communication technologies usage during the postgraduate period in the teaching and educational activity are examined in the article, as well as some peculiarities of teachers’ preparation to the effective usage of modern tutorials and information and communication technologies through special problem thematic courses in Postgraduate Pedagogical Education Institute are observed.